Multilayer crossed nanofiber membrane and preparation method thereof

By tanning and abandoning Luo Fei fish skin, multi -layered cross -nanofibrical membrane is prepared, the problem of low material brittleness and performance in the existing nanomang technology is solved, and high -efficiency ion transmission and excellent mechanical properties are achieved.

CN119368026APending Publication Date: 2025-01-28SUZHOU INST FOR ADVANCED STUDY USTC +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411681082.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In existing nanofluid technologies, the problems of material brittleness, lower performance or higher cost limit ionic conductivity and application stability.

Method used

Through tannas, the collagen crude fiber is divided into collagen nano -fiber, and a multi -layer cross -nanofiber film is obtained through abandoned treatment. The membrane has a multi -layer mesh structure and nano -fluid transmission of the same sex.

Benefits of technology

Realizing efficient ion transmission, with excellent mechanical strength and flexibility, the conductivity is within the range of 1 × 10-4 ~ 5 × 10-4s/cm, and is suitable for multi-directional nanotoscope applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368026A_ABST
    Figure CN119368026A_ABST
Patent Text Reader

Abstract

The invention provides a multilayer crossed nanofiber membrane and a preparation method thereof, and belongs to the technical field of fiber membranes. The multilayer crossed nanofiber membrane comprises a multilayer net structure formed by arranging a plurality of adjacent single-layer ordered nanofiber layers in a crossed manner, nanofibers are highly oriented on the single layer, and a nanochannel is formed between the adjacent nanofibers, so that the nanofiber membrane has an isotropic nanofluid transmission behavior.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fiber membranes and nanofluids, and in particular relates to a multi-layered cross-nanofiber membrane and a preparation method thereof, and more specifically relates to an ion transport membrane with isotropic nanofluid behavior and a preparation method thereof. Background Art

[0002] Ion-regulating nanofluidic membranes are widely used in desalination, osmotic energy generation, ion or molecular separation, and ionic circuits. The transport of ions in these membranes differs significantly from their behavior in the bulk phase due to the interaction of solvated ions with the inner walls of the membrane channels. The nanofluidic effect can be achieved at low concentrations (<10 -4 M) Provide higher ionic conductivity in electrolyte solutions, which is crucial for ionic circuits and nanofluidic ion transport membranes. Although silicon-based materials can produce aligned nanochannels through photolithography, their brittleness limits flexible applications. Although low-cost nanoporous polymer membranes have achieved remarkable success in industry, the three-dimensional tortuous nanoporous structure limits ionic conductivity. Two-dimensional nanofluidic devices based on boron nitride, graphene and MoS2, although they have excellent conductivity, the material processing process is relatively complex and expensive, and the structural fragility limits the stability of the performance of two-dimensional nanofluidic devices. Therefore, efficient ion regulation technology requires the search for higher performance and more sustainable nanomaterials. Summary of the invention

[0003] In view of this, the present invention provides a multi-layered cross-nanofiber membrane and a preparation method thereof, in order to at least partially solve one of the above technical problems. Therefore, the technical solution provided by the present invention is as follows.

[0004] As the first aspect of the present invention, a multilayer cross-nanofiber membrane is provided, comprising: a multilayer mesh structure composed of a plurality of adjacent single-layer ordered nanofiber layers arranged crosswise, wherein the nanofibers are highly oriented on the single layer and nanochannels are formed between adjacent nanofibers, so that the nanofiber membrane has isotropic nanofluid transmission behavior.

[0005] As a second aspect of the present invention, a method for preparing the above-mentioned multilayer cross-nanofiber membrane is provided, comprising: tanning the pretreated tilapia skin to differentiate the collagen crude fibers in the fish skin into collagen nanofibers; removing the fat in the tanned fish skin to obtain the multilayer cross-nanofiber membrane.

[0006] Based on the above technical solution, the present invention provides a multi-layered cross-nanofiber membrane and a preparation method thereof, which has at least one of the following beneficial effects:

[0007] (1) In an embodiment of the present invention, in a single layer, nanofibers are arranged in an orderly manner to form a single-layer nanofiber membrane, in which the nanofibers are highly oriented in one direction, and multiple adjacent single-layer ordered nanofiber layers are cross-arranged to form a multi-layer cross-nanofiber membrane with a multi-layer mesh structure, so that the multi-layer cross-nanofiber membrane is highly oriented. In the multi-layer cross-nanofiber membrane of the present invention, multiple adjacent single-layer ordered nanofiber layers are cross-arranged to form a mesh structure, the nanofibers are highly oriented on the single layer, and nanochannels are formed between two adjacent nanofibers in the single-layer ordered nanofiber layer to achieve ion transmission; and there are nanopores (or nanochannels) between two adjacent single-layer ordered nanofiber layers, which can also achieve ion transmission, so that the multi-layer cross-nanofiber membrane has isotropic nanofluid transmission behavior, that is, on the multi-layer cross-nanofiber membrane, the nanofluid transmission behavior in all directions is the same.

[0008] (2) In the embodiments of the present invention, tilapia skin is used as raw material due to its special microstructure, and collagen crude fibers in the skin are differentiated into collagen nanofibers by tanning, and then degreased to obtain a multilayer cross-nanofiber membrane. The preparation method of the present invention is relatively simple, and it is expected that tilapia skin can be applied to the field of nanofluids. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 This is a schematic diagram of the process of preparing a multilayer cross-nanofiber membrane based on tilapia skin in Example 1 of the present invention;

[0010] Figure 2 The present invention is a physical image of the descaled tilapia skin and a microscopic scanning electron microscope (SEM) image of the freeze-dried descaled tilapia skin in Example 1, wherein a is a physical image of the descaled tilapia skin, b is a cross-sectional microscopic morphology image of the freeze-dried descaled tilapia skin, and c is a surface microscopic morphology image of the freeze-dried descaled tilapia skin;

[0011] Figure 3 is a microscopic SEM image of the tanned tilapia skin in Example 1 of the present invention, wherein a is a cross-sectional microscopic morphology image of the freeze-dried tanned tilapia skin, and b is a surface microscopic morphology image of the freeze-dried tanned tilapia skin;

[0012] Figure 4 This is a SEM image of a multilayer cross-collagen nanofiber membrane after room temperature drying in Example 1 of the present invention, wherein a is a partial enlarged image of the cross-sectional microstructure of tilapia skin after tanning, and b is a partial enlarged image in the box of a;

[0013] Figure 5 is a transmittance diagram of the multi-layered crossed nanofiber membrane in Example 1 of the present invention;

[0014] Figure 6This is a comparison diagram of the mechanical strength of tilapia skin at different positions before and after treatment in Example 1 of the present invention;

[0015] Figure 7 The infrared spectra of tilapia skin before and after treatment in Example 1 of the present invention are shown;

[0016] Figure 8 This is a pore size distribution diagram of the multilayer cross-nanofiber membrane in Example 1 of the present invention;

[0017] Fig. 9 Schematic diagram of ionic conductivity measurement using a multi-layered cross-nanofiber membrane as a nanofluid device in an embodiment of the present invention;

[0018] Fig.10 Graph showing the relationship between ionic conductivity and KCl concentration before and after treatment of tilapia skin in an embodiment of the present invention;

[0019] Fig.11 This is a mechanism analysis diagram of the isotropic ion transport behavior of multilayered cross-nanofiber membrane. DETAILED DESCRIPTION

[0020] Below, embodiments of the present invention will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of embodiments of the present invention. However, it is apparent that one or more embodiments may also be implemented without these specific details. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion of concepts of the present invention.

[0021] The terms used herein are only for describing specific embodiments and are not intended to limit the present invention. The term "comprising" used herein indicates the existence of features, steps, operations, but does not exclude the existence or addition of one or more other features.

[0022] In the case of using expressions such as "at least one of A, B, and C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, and C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.). In the case of using expressions such as "at least one of A, B, or C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, or C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.).

[0023] At present, silicon-based materials, porous polymer membranes, graphene, MoS2 and other materials have problems of brittleness, low performance or high cost, and the three-dimensional tortuous nanoporous structure limits the ionic conductivity. Therefore, it is necessary to find higher performance and more sustainable materials suitable for ion regulation technology. Inspired by nature, natural wood has oriented nanocellulose fibers. After delignification, nanofluid devices are obtained through modification and densification processes (such as hot pressing, epoxy resin filling, etc.). Another example is the soft tissue of biological tissues such as muscle and cartilage, which are composed of biogels and have ordered structures and highly anisotropic properties. However, the unidirectional ordered nanochannel structures of wood, muscle, etc. can only achieve enhanced ion transport in a single direction, and it is difficult to adapt to regionalized efficient nanofluid transport, that is, it can only achieve single point-to-point rapid ion transport, and it is difficult to achieve rapid ion transport between any points in the region, which limits the practical application of nanofluid devices.

[0024] In the process of implementing the concept of the present invention, it was found that the fish in the water face a more complex water environment than the air environment, and the fish skin is also given more functions accordingly. The present invention is inspired by tilapia skin. By tanning the fish skin of tilapia, the collagen crude fibers are differentiated into nano-scale collagen nanofibers, and then the nanofiber membrane is obtained after degreasing. The nanofiber membrane has a multi-layer mesh structure, and the nanofibers in the single-layer nanofiber membrane are oriented in the same direction, so that the nanofiber membrane has isotropic nanofluid transmission behavior, so that it can be used for efficient nanofluid transmission, and at the same time has broad application prospects in the fields of energy, environment, and medical treatment.

[0025] Specifically, as the first aspect of the present invention, a multilayer cross-nanofiber membrane is provided, comprising: a multilayer mesh structure composed of a plurality of adjacent single-layer ordered nanofiber layers arranged crosswise, wherein the nanofibers are highly oriented on the single layer and nanochannels are formed between adjacent nanofibers, so that the nanofiber membrane has isotropic nanofluid transmission behavior.

[0026] In an embodiment of the present invention, nanofibers are arranged in an orderly manner to form a single-layer nanofiber membrane, and a plurality of adjacent single-layer ordered nanofiber layers are arranged in an orderly manner in a cross-shaped manner to form a multi-layer cross-shaped nanofiber membrane having a multi-layer mesh structure. The nanofibers of the multi-layer cross-shaped nanofiber membrane are highly oriented on a single layer, and nanochannels are formed between two adjacent nanofibers in a single-layer nanofiber layer, and there are nanopores between two adjacent nanofiber layers between layers, which can realize ion transmission, so that the multi-layer cross-shaped nanofiber membrane can realize ion transmission between layers while realizing ion transmission within the membrane, and has isotropic nanofluid transmission behavior, that is, on the multi-layer cross-shaped nanofiber membrane, fast ion transmission can be realized between any points in the nanofiber membrane area, and the ion transmission behavior of the nanofluid in all directions is the same.

[0027] According to an embodiment of the present invention, the nanofibers are collagen nanofibers, and polymer nanofibers prepared by other processes may also be used.

[0028] According to an embodiment of the present invention, the diameter of the nanofiber is 10-100nm, and the pore size of the nanochannel is 1nm-100nm, so as to ensure that the multi-layered cross-nanofiber membrane has good mechanical properties while maintaining a high ion transmission rate and conductivity. That is, the multi-layered cross-nanofiber membrane provided by the present invention is flexible in all directions and has a mechanical strength greater than 100MPa. The total thickness of the multi-layered cross-nanofiber membrane is 0.05mm-0.5mm, and the number of layers is 2-30, which can meet the current nanofluidic membrane's need for toughness and solve the brittleness problem of current silicon-based materials or two-dimensional nanofluidic devices of boron nitride, graphene and MoS2. Furthermore, the multi-layered cross-nanofiber membrane of the present invention has a mechanical strength of more than 100MPa in all directions. -4 ~10 -6 M, the conductivity in all directions is 1×10 -4 ~5×10 -4 S / cm, indicating that it has efficient ion transport in all directions.

[0029] According to the embodiments of the present invention, the light transmittance of the multi-layered cross-nanofiber membrane in the present invention is greater than 80%, which helps to broaden the application scenarios of nanofluids.

[0030] According to an embodiment of the present invention, the multi-layered crossed nanofiber membrane of the present invention can be used as an ion regulating nanofluidic membrane.

[0031] The method for preparing the multilayer cross-nanofiber membrane in the above embodiment comprises: tanning the pretreated tilapia skin to differentiate the collagen crude fibers in the fish skin into collagen nanofibers; removing the fat in the tanned fish skin to obtain the multilayer cross-nanofiber membrane.

[0032] In an embodiment of the present invention, tilapia skin is used as a raw material, and collagen crude fibers in the fish skin are differentiated into collagen nanofibers through tanning, and then a multilayer cross nanofiber membrane is obtained through degreasing treatment. The obtained multilayer cross nanofiber membrane still retains the special microstructure inherent in tilapia skin. In other words, the multilayer cross nanofiber membrane prepared by the present invention is composed of a plurality of single-layer ordered nanofiber layers arranged in an orderly manner to form a multilayer mesh structure, in which the single-layer nanofiber layer is highly ordered in one direction, so that a nanochannel is formed between two adjacent nanofibers; and a plurality of adjacent single-layer ordered nanofiber layers are arranged in an orderly manner and a nanochannel is formed between two adjacent nanofiber layers, which can realize ion transmission, so that the nanofiber membrane has an isotropic nanofluid transmission behavior. In addition, the preparation method of the present invention is relatively simple, and it is expected to apply tilapia skin to the field of nanofluids.

[0033] According to an embodiment of the present invention, pretreatment of tilapia includes: descaling and / or defatting. Specifically, the scales on the surface of the tilapia are removed; then the tilapia skin after descaling is immersed in a degreasing liquid and stored at 4°C for 12-48 hours to remove the fat in the skin. After repeated washing, it is set aside. Among them, the degreasing liquid used in the degreasing process of tilapia skin includes: 0.1-1% alkali solution or 5%-20% alcohol. Specifically, the degreasing liquid can be selected from 0.5% NaOH or 10% isopropanol or 10% butanol. The degreasing liquid needs to be replaced every 3-12 hours during the degreasing process. After degreasing, it is repeatedly washed with ethanol and water to remove excess grease.

[0034] According to an embodiment of the present invention, the treated tilapia skin is tanned to differentiate the collagen crude fibers in the fish skin into collagen nanofibers. The tanning time is 5-10 days, and the mass ratio of the tanning solution to the fish skin is 2:1-10:1, so as to fully achieve the differentiation of the collagen crude fibers in the fish skin. Further, the tanning solution includes: water and a tanning agent, wherein the tanning agent includes: at least one of alum, sodium chloride, chromate, and tannic acid, and the mass ratio of the tanning agent to water is 7:100-1:25. For example, the tanning solution includes alum, sodium chloride and water (which may be deionized water or ultrapure water) in a mass ratio of 3-5:3-5:100. Specifically, the tanning solution is prepared with a mass ratio of alum, sodium chloride and water of 5:5:100, and then the tanning treatment is performed at a mass ratio of 5:1 between the tanning solution and the tilapia skin. For another example, the tanning solution is prepared with a mass ratio of chromate to water of 1:20. For another example, the tanning solution is prepared with a mass ratio of tannic acid to water of 1:25.

[0035] Further, according to an embodiment of the present invention, after tanning the tilapia skin, fat in the tanned fish skin is removed with a scraper. Finally, ethanol and water are used alternately for washing to remove impurities in the fish skin and retain transparent collagen nanofibers.

[0036] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings.

[0037] In the present invention, a scanning electron microscope (SEM) is used to observe the morphological changes of tilapia skin. Fourier transform infrared spectroscopy (FTIR) is used to observe the group changes on the surface of collagen nanofibers during the tanning process of tilapia skin. A universal material testing machine is used to observe the strength changes of tilapia skin. The formation of nanochannels in tilapia skin is observed using a specific surface area determination method (BET). Two homemade Ag / AgCl electrodes and devices are used to perform current-voltage tests, and the tilapia skin before and after treatment needs to be immersed in an electrolyte for at least one day before the test.

[0038] Example 1

[0039] Figure 1 This is a schematic diagram of the process of preparing a multilayer cross-nanofiber membrane based on tilapia skin in Example 1 of the present invention.

[0040] like Figure 1 As shown, the method for preparing the multilayer cross-nanofiber membrane in the above embodiment comprises: removing the scales of tilapia, peeling off the complete fish skin and immersing it in a 0.5% NaOH degreasing solution, replacing the degreasing solution every 6 hours, and storing it at 4° C. for 18 hours for degreasing. After degreasing, the excess grease is removed by repeated washing with deionized water and ethanol.

[0041] A tanning solution was prepared with a mass ratio of alum, sodium chloride and deionized water of 5:5:100. Subsequently, the defatted tilapia skin was immersed in the tanning solution with a mass ratio of tanning solution to wet tilapia skin of 5:1, poured into a three-necked flask, and vigorously stirred at a speed of 500 rpm by a polytetrafluoroethylene stirring rod. Tanning was performed for 7 days until the collagen crude fibers were completely differentiated into nano-scale collagen nanofibers.

[0042] The fat on the surface of the tanned tilapia skin was scraped off with a knife, and the excess impurities were washed away using deionized water and ethanol to retain the transparent collagen fiber membrane, thereby obtaining a multilayer cross-nanofiber membrane (i.e., the treated tilapia skin).

[0043] Example 2

[0044] Example 2 The multilayered crossed nanofiber membrane was prepared by the same method as in Example 1. The specific preparation process is as follows:

[0045] The tilapia was descaled, the intact fish skin was peeled off and immersed in a 10% butanol degreasing solution, the degreasing solution was changed every 12 hours, and the fish was stored at 4°C for 48 hours for degreasing. After degreasing, the fish was repeatedly washed with deionized water and ethanol to remove excess oil.

[0046] A tanning solution was prepared with a mass ratio of alum, sodium chloride, and deionized water of 4:3:100. The mass ratio of the tanning solution to the wet tilapia skin was 10:1. The defatted tilapia skin was immersed in the tanning solution and poured into a three-necked flask, and vigorously stirred at a speed of 500 rpm using a polytetrafluoroethylene stirring rod. Tanning was performed for 1 day until the collagen crude fibers were differentiated into nano-scale collagen nanofibers.

[0047] The fat on the surface of the tanned tilapia skin was scraped off with a knife, and the excess impurities were washed away with deionized water and ethanol to retain the transparent collagen fiber membrane, thereby obtaining a multilayered cross-nanofiber membrane.

[0048] Example 3

[0049] Example 3 The multilayered cross-nanofiber membrane was prepared by the same method as in Example 1. The specific preparation process is as follows:

[0050] The tilapia was descaled, the intact fish skin was peeled off and immersed in a 10% isopropanol degreasing solution, the degreasing solution was changed every 3 hours, and the fish was stored at 4°C for 12 hours for degreasing. After degreasing, the fish was repeatedly washed with deionized water and ethanol to remove excess oil.

[0051] The tanning solution was prepared with a mass ratio of chromate to deionized water of 1:20. The mass ratio of the tanning solution to wet tilapia skin was 2:1. The defatted tilapia skin was immersed in the tanning solution and poured into a three-necked flask, and then pounded by rotating. The tanning was performed for 0.5 days until the collagen crude fibers were differentiated into nano-scale collagen nanofibers.

[0052] The fat on the surface of the tanned tilapia skin was scraped off with a knife, and the excess impurities were washed away using deionized water and ethanol to retain the transparent collagen fiber membrane, thereby forming a multi-layered cross-nanofiber membrane.

[0053] Example 4

[0054] Example 4 The multilayered crossed nanofiber membrane was prepared by the same method as in Example 1. The specific preparation process is as follows:

[0055] The tilapia was descaled, the intact fish skin was peeled off and immersed in a 0.5% NaOH degreasing solution, the degreasing solution was changed every 6 hours, and the fish was stored at 4°C for 24 hours for degreasing. After degreasing, the fish was repeatedly washed with deionized water and ethanol to remove excess oil.

[0056] A tanning solution was prepared with a mass ratio of tannic acid to deionized water of 1:25. Subsequently, the defatted tilapia skin was immersed in the tanning solution with a mass ratio of tanning solution to wet tilapia skin of 8:1, poured into a three-necked flask, and vigorously stirred at a speed of 500 rpm using a polytetrafluoroethylene stirring rod. Tanning was performed for 10 days until the collagen crude fibers were completely differentiated into nano-scale collagen nanofibers.

[0057] The fat on the surface of the tanned tilapia skin was scraped off with a knife, and the excess impurities were washed away with deionized water and ethanol to retain the transparent collagen fiber membrane, thereby obtaining a multilayered cross-nanofiber membrane.

[0058] The multi-layered cross-nanofiber membrane can be obtained by degreasing, tanning and re-degreasing tilapia skin using the methods in Examples 1 to 4 above.

[0059] Furthermore, scanning electron microscopy (SEM) was used to observe the microscopic morphological changes of tilapia skin before and after treatment. Figure 2-Figure 4 shown.

[0060] Figure 2 The present invention is a physical image of the descaled tilapia skin and a microscopic scanning electron microscope (SEM) image of the freeze-dried descaled tilapia skin in Example 1, wherein a is a physical image of the descaled tilapia skin, b is a cross-sectional microscopic morphology image of the freeze-dried descaled tilapia skin, and c is a surface microscopic morphology image of the freeze-dried descaled tilapia skin; Figure 3 It is a microscopic SEM image of the tanned tilapia skin in Example 1 of the present invention, wherein a is a cross-sectional microscopic morphology image of the freeze-dried tanned tilapia skin, and b is a surface microscopic morphology image of the freeze-dried tanned tilapia skin.

[0061] like Figure 2-Figure 3 As shown in the figure, macroscopically, the surface of the scaled tilapia skin has a grid-like structure; microscopically, in the treated tilapia skin (i.e., the multi-layered cross-nanofiber membrane), the collagen nanofibers in the single layer are highly ordered, and multiple single-layer nanofiber layers are cross-arranged to form a multi-layered cross-nanofiber membrane with a multi-layered mesh structure. In other words, from the cross-sectional microscopic morphology, it can be seen that the multiple single-layer collagen nanofiber membranes in the transverse section are orderly arranged, and intersect with the longitudinal collagen nanofiber membranes and are orderly arranged to form a multi-layered mesh structure. In addition, after the fat cells are removed from the tanned tilapia skin, a porous multi-layered cross-collagen nanofiber membrane is formed.

[0062] Figure 4 This is a SEM image of the multilayered cross-collagen nanofiber membrane after room temperature drying in Example 1 of the present invention, wherein a is a local enlarged image of the cross-sectional microstructure of tilapia skin after tanning, and b is a local enlarged image in the box of a.

[0063] like Figure 4 As shown in the partial enlarged image, it can be seen that the tanned collagen crude fibers differentiate into collagen nanofibers with a diameter of 10-100 nm, and it can be seen that there are multiple parallel collagen nanofibers in the single layer of collagen nanofibers (that is, the nanofibers in the single layer are arranged in an orderly manner, and the nanofibers are highly oriented on the single layer), and the adjacent single layers of collagen nanofiber membranes are cross-arranged to form a network structure (such as Figure 4 b) in the above.

[0064] Figure 5 Graph showing the transmittance of the multi-layered cross-nanofiber membrane in Example 1 of the present invention. Figure 5 As shown, the transmittance of the multi-layered cross-nanofiber membrane prepared from tilapia skin provided by the present invention can reach more than 80%.

[0065] Figure 6 This is a comparison diagram of the mechanical strength of tilapia skin at different positions before and after treatment in Example 1 of the present invention, wherein: Figure 6 Center orientation 1, orientation 2, and orientation 3 indicate the positions of No. 1, No. 2, and No. 3 in different directions of tilapia.

[0066] like Figure 6 As shown, due to the removal of impurities such as fat cells in the tilapia skin by tanning and degreasing, the strength and elongation at break of the obtained collagen nanofiber membrane in all directions are significantly enhanced, and the strength and elongation at break at all positions of the tilapia skin have the same change trend. This shows that the tilapia skin after tanning and degreasing has higher flexibility and mechanical strength, and the multi-layered cross-nanofiber membrane provided by the present invention has an isotropic property, and can also be called a multi-layered cross-oriented nanofiber membrane.

[0067] Furthermore, the surface groups of tilapia skin before and after treatment were observed to determine whether there were changes in its flexibility and mechanical strength due to changes in the groups. The specific group test results are as follows: Figure 7 shown.

[0068] Figure 7 This is the infrared spectra of tilapia skin before and after treatment in Example 1 of the present invention.

[0069] like Figure 7 As shown, the groups on the surface of the collagen nanomembrane of the tanned and degreased tilapia skin (i.e., treated tilapia skin) did not change significantly when compared with the untanned and degreased tilapia skin (tilapia skin), indicating that the change in the performance of the treated tilapia skin was not caused by the groups.

[0070] Further, the pore size of the multilayer cross-nanofiber membrane in Example 1 was analyzed, as shown in FIG. Figure 8 shown.

[0071] Figure 8 This is the pore size distribution diagram of the multi-layer cross-nanofiber membrane in Example 1 of the present invention.

[0072] like Figure 8 As shown, the pore sizes of the multi-layered cross-nanofiber membrane (i.e., the treated tilapia skin) of the present invention are mainly distributed below 100 nm, and more concentrated in 5-10 nm.

[0073] Furthermore, an ion transmission device was built to investigate the ion transmission characteristics of the multilayered cross-nanofiber membrane.

[0074] Fig. 9 Schematic diagram of ionic conductivity measurement using a multilayer cross-nanofiber membrane as a nanofluid device in an embodiment of the present invention.

[0075] like Fig. 9 As shown in the figure, KCl solution was added to the electrolytic cell as an ion transport solution, Ag / AgCl electrodes were installed on both sides of the electrolytic cell, polydimethylsiloxane (PDMS) was used to fix the multilayer cross nanofiber membrane, and the gap in the middle was filled to divide the electrolytic cell into two chambers. It should be noted that before the test, the multilayer cross nanofiber membrane (i.e., the treated tilapia skin), untanned, defatted tilapia skin, and the 10 -6 1 M KCl electrolyte for at least one day.

[0076] Fig.10 Graph showing the relationship between the ionic conductivity and KCl concentration of tilapia skin before and after treatment in an embodiment of the present invention.

[0077] like Fig.10 As shown in Figure 2, at high concentrations (0.01-1 M), the ionic conductivity increases linearly with the logarithm of the KCl concentration. At lower electrolyte concentrations (<0.01 M), it shows typical nanofluid ion transport behavior. -6 M, its conductivity limit is 2.4×10 -4 S / cm, which is significantly higher than that of untanned and / or defatted tilapia skin. This is attributed to the nanochannels formed by collagen nanofibers and the cationic charge on the surface of the collagen nanofiber membrane. The concentration of anions (main charge carriers) in the nanochannels increases, thereby significantly improving the ionic conductivity at low electrolyte concentrations (<0.01M). In addition, the multilayer cross-nanofiber membrane has similar ionic conductivity at different positions (such as orientation 1, orientation 2, and orientation 3), and exhibits the same ion output characteristics, which also shows that the multilayer cross-nanofiber membrane of the present invention has the same orientation at different positions, and can achieve efficient ion transmission behavior between any points in the multilayer cross-nanofiber membrane.

[0078] Fig.11This is a mechanism analysis diagram of the isotropic ion transport behavior of multilayered cross-nanofiber membrane.

[0079] like Figure 1 As shown in the figure, for the disordered nanofiber membrane, the fibers inside it are arranged disorderly, resulting in ion transport along a tortuous path from point A to point B and from point A to point C in the disordered nanofiber membrane. For the unidirectional ordered nanofiber membrane, the nanofibers inside the membrane are arranged in an orderly manner along a single direction, and fast ion transport can be achieved along the direction of nanofiber arrangement, that is, from point A to point B, but for point A to point C, fast ion transport cannot be achieved. As for the multi-layer cross-nanofiber membrane in the present invention, it has a multi-layer mesh structure composed of multiple adjacent single-layer ordered nanofiber layers arranged crosswise, and the nanofibers in the single-layer nanofiber layer are highly oriented and nanochannels are formed between adjacent nanofibers. There are also nanopores (or nanochannels) between adjacent single-layer ordered nanofiber layers, that is, there are nanochannels between the two layers of gaps where the horizontal single-layer ordered nanofiber layer and the longitudinal single-layer ordered nanofiber layer are cross-stacked), which can realize bidirectional or multi-directional ion transport, and the nanofibers are highly oriented on the single layer, so that the nanofiber membrane has isotropic nanofluid transport behavior, that is, it realizes rapid ion transport from point A to point B or point C, and the ion conductivity between point A to point B and point A to point C is the same.

[0080] In summary, compared with the rigidity of silicon-based nanofluid devices and the high unidirectional strength of wood nanofluids, the multilayered cross-nanofiber membrane obtained by processing tilapia skin has excellent flexibility and mechanical strength in all directions (>100MPa), and it has nanochannels less than 100nm. Due to the cross-arrangement of multiple single-layer ordered nanofiber layers and the nanochannels formed by the highly oriented collagen nanofibers in the single layer, the multilayered cross-nanofiber membrane has similar efficient ion transport behavior, with a 1×10 -4 ~5×10 -4 The high ionic conductivity of 1000 S / cm is several orders of magnitude higher than that of bulk KCl solution of the same concentration. This indicates that it has efficient ion transport in all directions, narrowing the application limitations and increasing its application in other technological fields.

[0081] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A multi-layered cross-nanofiber membrane, comprising: A multilayer network structure composed of a plurality of adjacent single-layer ordered nanofiber layers arranged crosswise, wherein the nanofibers are highly oriented on the single layer and nanochannels are formed between adjacent nanofibers, so that the nanofiber membrane has isotropic nanofluid transmission behavior.

2. The multilayered crossed nanofiber membrane according to claim 1, wherein: The nanofibers are collagen nanofibers.

3. The multi-layered crossed nanofiber membrane according to claim 1, wherein: The diameter of the nanofiber is 10-100 nm, and the pore size of the nanochannel is 1 nm-100 nm.

4. The multi-layered crossed nanofiber membrane according to claim 1, wherein: The multi-layered cross-nanofiber membrane is flexible in all directions and has a mechanical strength greater than 100 MPa. The total thickness of the multi-layered cross-nanofiber membrane is 0.05 mm-0.5 mm, and the number of layers is 2-30.

5. The multi-layered crossed nanofiber membrane according to claim 1, wherein: The light transmittance of the multi-layered cross-nanofiber membrane is greater than 80%.

6. The multi-layered crossed nanofiber membrane according to claim 1, wherein: The multilayered cross-nanofiber membrane is in an ionic solution with a concentration of 10 -4 ~10 -6 M, the conductivity in all directions is 1×10 -4 ~5×10 -4 S / cm.

7. The multi-layered crossed nanofiber membrane according to claim 1, which is used as an ion regulating nanofluidic membrane.

8. A method for preparing a multilayer crossed nanofiber membrane according to any one of claims 1 to 7, comprising: Tanning the pretreated tilapia skin to differentiate collagen macrofibers in the skin into collagen nanofibers; The fat in the fish skin after tanning is removed to obtain a multi-layered cross-nanofiber membrane.

9. The method according to claim 8, wherein: The tanning time is 5-10 days, and the mass ratio of the tanning solution to the fish skin is 2:1-10:1; Wherein, the tanning solution comprises water and a tanning agent, and the tanning agent comprises at least one of alum, sodium chloride, chromate, and tannic acid; Wherein, the mass ratio of the tanning agent to water is 7:100-1:

25.

10. The method according to claim 8, wherein: The pretreatment includes: descaling and / or degreasing; Wherein, the degreasing liquid used in the degreasing process includes: 0.1%-1% alkali solution or 5%-20% alcohol.